A strategy for actualization of active targeting nanomedicine practically functioning in a living body. (October 2017) - Lee, Kyoung Jin; Shin, Seol Hwa; Lee, Jae Hee; Ju, Eun Jin; Park, Yun-Yong; Hwang, Jung Jin; Suh, Young-Ah; Hong, Seung-Mo; Jang, Se Jin; Lee, Jung Shin; Song, Si Yeol; Jeong, Seong-Yun; et al.
Abstract: Designing nanocarriers with active targeting has been increasingly emphasized as for an ideal delivery mechanism of anti-cancer therapeutic agents, but the actualization has been constrained by lack of reliable strategy ultimately applicable. Here, we designed and verified a strategy to achieve active targeting nanomedicine that works in a living body, utilizing animal models bearing a patient's tumor tissue and subjected to the same treatments that would be used in the clinic. The concept for this strategy was that a novel peptide probe and its counterpart protein, which responded to a therapy, were identified, and then the inherent ability of the peptide to target the designated tumor protein was used for active targeting in vivo . An initial dose of ionizing radiation was locally delivered to the gastric cancer (GC) tumor of a patient-derived xenograft mouse model, and phage-displayed peptide library was intravenously injected. The peptides tightly bound to the tumor were recovered, and the counterpart protein was subsequently identified. Peptide-conjugated liposomal drug showed dramatically improved therapeutic efficacy and possibility of diagnostic imaging with radiation. These results strongly suggested the potential of our strategy to achieve in vivo functional active targeting and to be applied clinically for human cancer treatment.